UNGKAPAN LARANGAN DALAM ANIME SPY X FAMILY SEASON 1 KARYA TETSUYA ENDOU - Novi Amri Lipia Putri; Prisyanti Suciaty (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
prohibition expressions in Japan have different contexts based on the level of formality, and their relationship with the speaker and the other speaker. By understanding these differences, it is important to avoid misunderstandings and it is necessary to adjust the way of speaking to the right situation of the other person. This study aims to find out the various sentence patterns that form forbidden expressions and their use in the anime SPY x FAMILY Season 1 by Tetsuya Endou. This research is a qualitative research with a descriptive method. Qualitative research was chosen because the data studied was in the form of direct dialogue pieces and presented in the form of reports in the form of words and not numbers, so it did not require statistical calculations. The data collection technique used in this study is the look and note technique. This study uses theoretical triagulation in choosing sentence patterns that form prohibited expressions, as well as using context theory from Hymes. After data collection and analysis, 68 data were found, namely 54 data using ~na, 6 data using ~te wa ikemasen / ikenai, 1 data using ~te wa naranai, and 7 data using naide/naide kure/naide kudasai, as well as 0 data for sentence patterns ~nai koto and ~bekarazu. The ~na sentence pattern is more prominent in Tetsuya Endou's SPY x FAMILY Season 1 anime because of the language style used to describe the relationships between characters and situations in the story. Where there are often interactions that use a lot of affirmations, so the use of prohibition expressions with the suffix ~na helps to provide a clear affirmation of prohibition.